Mathematical Software -- ICMS 2014 4th International Conference, Seoul, South Korea, August 5-9, 2014, Proceedings - Hong, Hoon; Yap, Chee (Theoretical Computer Science and General Issues, 2014)
This book constitutes the proceedings of the 4th International Conference on Mathematical Software, ICMS 2014, held in Seoul, South Korea, in August 2014. The 108 papers included in this volume were carefully reviewed and selected from 150 submissions. The papers are organized in topical sections named: invited; exploration; group; coding; topology; algebraic; geometry; surfaces; reasoning; special; Groebner; triangular; parametric; interfaces and general.